Implementasi Kebijakan Kelas Ibu Hamil sebagai Bentuk Pemberdayaan Masyarakat dalam Upaya Penurunan Kematian Ibu di Kota Cimahi - Elin Marlina; Joni Dawud; Ayuning Budiarti (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2021)
This study aims to determine the implementation of the Regulation of the Minister of Health of the Republic of Indonesia Number. 97 of 2014 in the City of Cimahi regarding the class of pregnant women. Qualitative methods are used to answer problems related to the implementation of the policy. Types of data consist of secondary data and primary data collected through interviews, document review and observation. The results of this study indicate that the implementation of the class policy for pregnant women has not been effectively implemented in Cimahi City because the maternal mortality rate is still relatively high. This ineffectiveness is due to the fact that the participation of pregnant women in attending classes for pregnant women is not optimal, with the constraints of not optimal family support. The target class for pregnant women is still lacking. Apart from that, the facilities and infrastructure are still limited as well as the allocated budget. In order to improve the implementation of this policy in the future, it is hoped that the empowerment of cadres and all communities. Puskesmas made innovations in providing class materials for pregnant women.